The Effect of Microprudential Policies on the Profitability of Conventional Banks - Qoriroh, Nisrina; Aminullah Achmad Muttaqin (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to examine the relationship between microprudential policies and the variables LDR, NPL, CAR, CIR, and Dummy_GCG on profitability in conventional banking in Indonesia. This study provides insights into the impact of microprudential policies focused on bank health and corporate governance on bank profitability. The study employs quantitative methods and panel data regression. The data used in this study are secondary data obtained from the annual financial reports of conventional banks using purposive sampling. The sample consists of 9 conventional banks with a study period from 2017 to 2023. The results show that microprudential policies with the LDR variable have a positive and insignificant effect on ROA and ROE, the NPL variable has a negative and significant effect on ROA and ROE, the CAR variable has a negative effect on ROA and a positive but insignificant effect on ROE, the CIR variable has a negative and significant effect on ROA and ROE, and the Dummy_GCG variable has a positive and insignificant effect on ROA and ROE. Simultaneously, LDR, NPL, CAR, CIR, and Dummy_GCG affect the profitability of conventional banks.